2009
DOI: 10.1016/s0025-6196(11)60561-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and Managing All Aspects of Migraine: Migraine Attacks, Migraine-Related Functional Impairment, Common Comorbidities, and Quality of Life

Abstract: Migraine can be characterized as a chronic disorder with episodic attacks and the potential for progression to chronic migraine. We conducted a PubMed literature search (January 1, 1970 through May 31, 2008) for studies on the impact of migraine, including disability, health-related quality of life (HRQoL), comorbidities, and instruments used by health care professionals to treat patients with migraine. Numerous studies have shown that migraine substantially impairs a person's functions during attacks and dimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(126 citation statements)
references
References 115 publications
3
122
0
1
Order By: Relevance
“…Teaching on primary headaches should be improved, though not only quantitatively increasing the passive time devoted to these entities in the lecture rooms, but also qualitatively educating doctors in active strategies, which have been shown to improve medical communication [28]. In primary headaches, where diagnosis is based on reported symptoms and where treatment success largely depends on patient compliance, these strategies have demonstrated to improve diagnosis and patient satisfaction without adding time to the medical visit [29].…”
Section: Discussionmentioning
confidence: 99%
“…Teaching on primary headaches should be improved, though not only quantitatively increasing the passive time devoted to these entities in the lecture rooms, but also qualitatively educating doctors in active strategies, which have been shown to improve medical communication [28]. In primary headaches, where diagnosis is based on reported symptoms and where treatment success largely depends on patient compliance, these strategies have demonstrated to improve diagnosis and patient satisfaction without adding time to the medical visit [29].…”
Section: Discussionmentioning
confidence: 99%
“…The usual age of onset is 12 to 17 years of age for females and 5 to 11 years for males with incidence of migraine with aura cresting earlier in this range for both. In the American Migraine Study II, 92% of women and 89% of men with migraine reported some headache-related disability, and 53% were severely disabled or needed bed rest during an attack (Buse et al, 2009). Number of neurologic and psychiatric disorders, including epilepsy, stroke, major depression and anxiety disorder, show increased co-morbidity with migraine.…”
Section: Epidemiologymentioning
confidence: 99%
“…Therefore, special attention should be paid to both control and reduction of risk factors which might favor the chronicization process and/or the outbreak of MOH [40,41]. Among the risk factors for chronicization are non-changeable agents such as demography, age, and socio-economic status, as well as changeable factors, such as obesity and a specific psychological pattern (Table 1).…”
Section: Risk Factors and Chronicization Of Migrainementioning
confidence: 99%